2022
DOI: 10.3390/ijerph19031452
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations on Weight Loss and Healthy Lifestyle in Prostate Cancer Clinical Guidelines: A Systematic Review

Abstract: Obesity is associated with negative prostate cancer outcomes (e.g., specific mortality, all-cause mortality, biochemical recurrence, etc.), according to the current scientific literature. Nevertheless, recommendations on weight loss and healthy lifestyles are poorly covered by clinicians. We aimed at identifying these recommendations from clinical practice guidelines (CPGs) for prostate cancer. We systematically searched MEDLINE, EMBASE, Web of Science, Scopus, guideline databases and online sources for CPGs u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Additionally, a 2022 systematic review analyzing prostate cancer guidelines revealed a global deficiency in the emphasis on weight loss and healthy lifestyle practices among clinicians [ 35 ]. Despite the well-documented association between obesity and adverse prostate cancer outcomes, a negligible portion of these guidelines recommend weight maintenance or highlight the significance of a healthy lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a 2022 systematic review analyzing prostate cancer guidelines revealed a global deficiency in the emphasis on weight loss and healthy lifestyle practices among clinicians [ 35 ]. Despite the well-documented association between obesity and adverse prostate cancer outcomes, a negligible portion of these guidelines recommend weight maintenance or highlight the significance of a healthy lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…The "obesity paradox" debate that has occurred between the association of high body weight and cancer survival benefits and increased tolerance during some anticancer therapies may be explained by the association of obesity with subtypes of less aggressive tumors and other confounding factors, such as smoking and body composition [16]. Intervention studies predominantly conducted in breast, endometrial and prostate cancer trials showed positive effects of intentional weight loss based on diet composition, caloric intake and amount and nature of physical activity [19][20][21][22]. It is also known that bariatric surgery, achieving significant and long-term weight loss, is effective in reducing the incidence of obesity-associated cancer and the cancer-related mortality [23].…”
Section: Weight Loss and Cancer Risk And Prognosismentioning
confidence: 99%
“…Additionally, there is a moderate-consistent association between obesity and biochemical recurrence following radical prostatectomy [26]. Despite the role of obesity in prostate cancer, only a few prostate cancer guidelines recommend the adoption of a healthy lifestyle, and only 7.2% provide advice on reaching or maintaining a healthy weight [22].…”
Section: Weight Loss and Cancer Risk And Prognosismentioning
confidence: 99%
“…If the treatment time exceeds 2 years, the body will easily develop resistance to ADT, and almost all of patients will progress to castration-resistant prostate cancer in later stages or metastatic castration-resistant prostate cancer [ 6 ]. Once the disease progresses to castration-resistant prostate cancer, radiotherapy, chemotherapy, targeted therapy, and other methods are difficult to effectively slow down the progress of the disease; ADT usually produces many adverse reactions [ 7 ], reducing the quality of life of patients during treatment [ 8 ]. Therefore, modern medicine still has many deficiencies in the diagnosis and treatment of prostate cancer, and there is still a lack of effective treatment methods.…”
Section: Introductionmentioning
confidence: 99%